Effect of Evidence Based Medicine Education on Research and Critical Appraisal Skills of Midwifery Students in North Khorasan University of Medical Sciences - Mahbubeh Tabatabi (Babol University of Medical Sciences, 2013)
ABSTRACT BACKGROUND AND OBJECTIVE: Evidence Based Medicine (EBM) is a set of methods and resources for finding and employing the best evidences among present in order to manage each patient. The aim of this study was to determine the effect of Evidence Based Medicine on research and critical appraisal skills of midwifery students. METHODS: This study was performed among gynecology clerkship students in Bojnurd University of Medical Sciences. Sampling was easy and purposeful. Midwifery students enrolled in an EBM workshop. A standard questionnaire was used before and after the workshop for data collection. FINDINGS: According to the findings a significant change was observed in critical appraisal skill. CONCLUSION: Workshop and discussion on research articles and specific cases can increase the assessing and critical appraisal skills among students.